2016
DOI: 10.12688/f1000research.8300.2
|View full text |Cite
|
Sign up to set email alerts
|

Complex mechanisms linking neurocognitive dysfunction to insulin resistance and other metabolic dysfunction

Abstract: Scientific evidence has established several links between metabolic and neurocognitive dysfunction, and epidemiologic evidence has revealed an increased risk of Alzheimer’s disease and vascular dementia in patients with diabetes. In July 2015, the National Institute of Diabetes, Digestive, and Kidney Diseases gathered experts from multiple clinical and scientific disciplines, in a workshop entitled “The Intersection of Metabolic and Neurocognitive Dysfunction”, to clarify the state-of-the-science on the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 152 publications
(180 reference statements)
3
66
0
2
Order By: Relevance
“…Even small advances may offer the opportunity to have an important influence on decreasing the large and growing burden of two of the most important public health challenges of the 21st century. Collaborative efforts, across different scientific disciplines and across all stakeholders including the public and governmental agencies, are underway to move toward improving the lives of those with, or at risk for, T2D and dementia .…”
Section: Discussionmentioning
confidence: 99%
“…Even small advances may offer the opportunity to have an important influence on decreasing the large and growing burden of two of the most important public health challenges of the 21st century. Collaborative efforts, across different scientific disciplines and across all stakeholders including the public and governmental agencies, are underway to move toward improving the lives of those with, or at risk for, T2D and dementia .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that metabolic syndrome (MetS) and its components are important risk factors of mild cognitive impairment, age-related cognitive decline, vascular dementia, and Alzheimer’s disease [4, 5]. Although some potential mechanisms have been proposed, there is still a big knowledge gap at identifying roles and molecular mechanisms that underlie obesity and other individual components of the MetS in developing predementia and dementia syndromes [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, it would also be very important to develop a newly proposed disease-course modification strategy toward early and effective risk factor management that could be clinically significant in reducing the risk of metabolic and cognitive decline [7]. Since individual risk factors or MetS components may independently impair metabolic and cognitive function, one ideal intervention approach is to simultaneously control multiple obesity-related metabolic dysfunction and pro-inflammatory pathways [7, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of brain insulin signaling is clinically relevant, since it has been reported that neuronal insulin signaling is impaired in dementia (Stoeckel et al . ); the reduction in IR expression by presenilin, and the repression of an active IR conformation by major histocompatibility complex class I, as mentioned in the previous section, were suggested to contribute to the causative role of presenilins and of brain inflammation in Alzheimer's disease (AD) (Maesako et al . ; Dixon‐Salazar et al .…”
Section: Ir In Alzheimer's Diseasementioning
confidence: 99%